1988
DOI: 10.1038/336692a0
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between fos and jun nuclear oncoproteins: role of the 'leucine zipper' domain

Abstract: Gene expression is modulated by the specific interactions of nuclear proteins with unique regulatory sequences in the genome. Proteins involved in transcriptional regulation seem to be either transcription factors or transcription modulators and their interactions are crucial in determining whether the expression of a specific gene is activated or repressed. Recently, the product of the proto-oncogene jun has been identified as the transcription factor AP-1, whereas nuclear oncoproteins fos and myc have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
201
0
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(213 citation statements)
references
References 19 publications
9
201
0
3
Order By: Relevance
“…These genes encode components of the AP1 transcription factor formed by homo-or hetero-dimerization of the Jun and Fos proteins. Dimerization occurs through a leucine-repeat located in the highly conserved C-terminal part of the Jun proteins or in an internal position in the Fos proteins (Landschulz et al, 1988;Sassone-Corsi et al, 1988a). As the Fos proteins do not form dimers among themselves, AP1 is a set of low a nity Jun/Jun and high a nity Jun/Fos dimers (Nakabeppu et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These genes encode components of the AP1 transcription factor formed by homo-or hetero-dimerization of the Jun and Fos proteins. Dimerization occurs through a leucine-repeat located in the highly conserved C-terminal part of the Jun proteins or in an internal position in the Fos proteins (Landschulz et al, 1988;Sassone-Corsi et al, 1988a). As the Fos proteins do not form dimers among themselves, AP1 is a set of low a nity Jun/Jun and high a nity Jun/Fos dimers (Nakabeppu et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…AP-1 is composed of Fos (Cohen and Curran, 1988;Zerial et al, 1989;Nishina et al, 1990;Matsui et al, 1990) and Jun family proteins (Nishimura and Vogt, 1988;Nathans, 1988, 1989;Hirai et al, 1989). Any member of Fos can form a heterodimeric complex with any member of Jun, and all the resultant complexes bind to speci®c DNA sequences known as AP-1 binding sites (Halazonetis et al, 1988;Sassone-Corsi et al, 1988;Nakabeppu et al, 1988;Suzuki et al, 1991b). Using dominant-negative mutants of Fos and Jun family proteins that function as general inhibitors of AP-1, we have previously shown that activation of endogenous AP-1 is essential for cellular transformation by a wide variety of transforming genes, such as vsrc, v-yes, v-fps, c-Ha-ras and activated by c-raf (Okuno et al, 1991;Suzuki et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have shown that the human AP-1 (activator protein 1) gene is the cellular homologue of the transforming v-jun gene [4,5]. The AP-I complexes consist of several distinct proteins ineluding those encoded by the proto-onco.~,-nes c-jun and c-fos, and other members in these two gene families [6][7][8][9][10]. At least two other members, jun-B and jun-D, have been identified in the jun family.…”
Section: Introductioi'imentioning
confidence: 99%